2007
DOI: 10.1080/14017430601150601
|View full text |Cite
|
Sign up to set email alerts
|

An alternative agent for radial arterial graft spasm: Application of topical iloprost

Abstract: Iloprost can be recommended as a strong alternative to the topical agents used for preventing arterial graft spasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…9,21 Other topical pharmacological agents, such as the synthetic prostacyclin iloprost and diltiazem, have also been explored. 25,27 However, the half-lives of these therapies are minutes to hours, and efficacy data on these techniques are limited. A uniform ex vivo treatment and postoperative protocol for EC-IC bypass graft spasm prevention does not currently exist.…”
Section: Discussionmentioning
confidence: 99%
“…9,21 Other topical pharmacological agents, such as the synthetic prostacyclin iloprost and diltiazem, have also been explored. 25,27 However, the half-lives of these therapies are minutes to hours, and efficacy data on these techniques are limited. A uniform ex vivo treatment and postoperative protocol for EC-IC bypass graft spasm prevention does not currently exist.…”
Section: Discussionmentioning
confidence: 99%
“…The ICER of iloprost has yet to be studied, and the cost benefit of iloprost in high‐risk populations who cannot be fluid resuscitated, such as those with acutely decompensated chronic heart failure and renal insufficiency who must undergo coronary angiography, must be determined. Other potential benefits of iloprost include peripheral arterial vasodilatation during catheterization, and possibly prevention of arterial spasm …”
Section: Discussionmentioning
confidence: 99%
“…Another study showed the effects of iloprost as topical vasodilatation for the radial artery in 28 patients. In this study, iloprost, papaverine, diltiazem, and placebo-controlled solutions and the contraction-relaxation response for the radial artery were evaluated and they concluded that the effects of vasodilatation on the radial artery of the topical iloprost were equivalent to that of dapper tissue and that iloprost could be routinely used as a topical vasodilator [33] .…”
Section: Iloprostmentioning
confidence: 99%